Influência da programação semafórica no comportamento dos pedestres : estudo de caso na cidade do Rio de Janeiro - Jambo, Lívia Brito (2018)
The most common pedestrian deviance in Brazilian traffic is traffic signal disrespect. Such behavior can lead to trampling, which is one of the main causes of violent deaths in Brazil. At the same time, the mobility of both pedestrians and vehicles is greatly affected, even when the trampling is not consummated; when it causes unplanned changes in vehicle trajectory, sudden braking and accidents with other vehicles. The purpose of this dissertation is the specific study of the influence of semaphoric programming on the traffic signal disrespect by pedestrians, which, along with several psychosocial factors, influence this behavior. As a data source and case study, the center of the city of Rio de Janeiro was adopted, notably the traffic lights located at the intersections of Presidente Vargas and Rio Branco avenues and between Rio Branco and Almirante Barroso avenues, from which were collected pedestrian and semaphores data. With the application of the Data Envelopment Analysis (DEA) method, using the input-oriented CCR model, it is evident the need to adapt the traffic signal programming for the case studied, with quantitative data on the necessary alteration of the semaphore periods . This methodology can be replicated to other similar cases in Rio de Janeiro.